Virus-Specific T Cell Therapies for HIV: Lessons Learned From Hematopoietic Stem Cell Transplantation - Lee, Ping-Hsien; Keller, Michael D.; Hanley, Patrick J.; Bollard, Catherine M. (Frontiers in Cellular and Infection Microbiology, 2020)
Human immunodeficiency virus (HIV) has caused millions of deaths and continues to threaten the health of millions of people worldwide. Despite anti-retroviral therapy (ART) substantially alleviating severity and limiting transmission, HIV has not been eradicated and its persistence can lead to other health concerns such as cancer. The only two cases of HIV cure to date are HIV+ cancer patients receiving an allogeneic hematopoietic stem cell transplantation (allo-HSCT) from a donor with the CCR5 Δ32 mutation. While this approach has not led to such success in other patients and is not applicable to HIV+ individuals without cancer, the encouraging results may point toward a breakthrough in developing a cure strategy for HIV. Adoptive transfer of virus-specific T cells (VSTs) post HSCT has been effectively used to treat and prevent reactivation of latent viral infections such as cytomegalovirus (CMV) and Epstein-Barr virus (EBV), making VSTs an attractive therapeutic to control HIV rebound. Here we will discuss the potential of using adoptive T cell therapies in combination with other treatments such as HSCT and latency reversing agents (LRA) to achieve a functional cure for HIV.